Religion and Cultural Factors in Bilateral Trade between Indonesia and ASEAN Member Countries - Waristi, Fino Valico (Badan kebijakan Fiskal, 2014)
This study focus on the roles of culture and religion in explaining the bilateral trade between Indonesia and the member of ASEAN countries. This research uses the theory of gravity (Gravity Model) by applying random effect and Pooled Regressions analysis in measuring the correlation between set variables. The tested variables are Indonesia's Real GDP, Real GDP of ASEAN countries, Distances, cost of trade, variable of Religion and Cultural factors, during the period of 2002 and 2011. We used secondary data from CEIC, CEPIl, and Hofstede index. The results show that religon does not significantly affect the bilateral trade, while culture similarity has tendencies to affect bilateral trade. Meanwhile, the result supports prior analysis that the distance variable has strong correlation to the bilateral trade. This study implies the need for further studies on the application of gravity models to explain bilateral trade within countries in the region.